The literal elements of Tholkappiyam in Tibetan grammars from a linguistic point of view: மொழியியல் நோக்கில் திபெத்திய இலக்கணங்களில் தொல்காப்பிய எழுத்தியல் கூறுகள் - M., Jothi letchumi (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2021)
World languages somehow share some common features. Linguist name them as universal grammatical laws. The very same features of a language could be seen in other languages as well. Likewise, there were some notable features could be seen shared by one of the classical languages, Tamil and Tibetian language. Besides studying the way of living of the Tibetan people, the paper also explore the resemblances between the languages, especially the basis of the phonetics of the Tibetan and Tamil languages as underlined by the oldest grammatical treatise that could be seen in Tamil, the Tholkappiyam. The author has tried to establish the similarities between these languages, by considering the historical references and from the literature. உலக மொழி இலக்கணங்களுக்கு இடையே உள்ள ஒற்றுமையையும், தமிழ் இலக்கணத்தின் மற்றொரு பரிணாமத்தையும், ஆராய வேண்டும் என்ற முயற்சியே இக்கட்டுரையின் நோக்கமாகும். திபெத் மக்களின் வாழ்வியல் பற்றியும், திபெத்திய இலக்கணங்களின் எழுத்தியல் கூறுகள் பற்றியும், தொல்காப்பிய இலக்கணத்தின் எழுத்தியல் கூறுகள் பற்றியும், இவை இரண்டுக்கும் இடையே உள்ள ஒற்றுமை குறித்தும், சான்றுகளுடன் ஆராய்ந்து அறியவும் இக்கட்டுரை முற்படுகின்றது. மேலும், தொல்காப்பிய இலக்கணத்தின் முன்னைய மரபு குறித்தும், அந்த மரபின் நீட்சியே திபெத்திய இலக்கணம் தோன்றுவதற்கான தோற்றுவாய் என்பது குறித்தும், வரலாற்றுச் சான்றுகள் வழியும், எழுத்தியல் கூறுகள் வழியும், மொழியியல் நோக்கில் நிரூபிக்க முற்படுவதே இக்கட்டுரையின் கருதுகோள் ஆகும்.